Fleksibilitas Pembelajaran di Sekolah Tinggi Ilmu Tarbiyah Raden Wijaya Mojokerto: Studi tentang Pembelajaran Pilihan Luring dan Daring Berdasarkan Kesepakatan Dosen bersama Mahasiswa - Afif, Muthoharun (Ta'dibia: Jurnal Ilmiah Pendidikan Agama Islam, 2019)
This article aims to describe: Learning Flexibility at Tarbiyah Raden Wijaya Mojokerto College of Learning about offline and online options based on the agreement between lecturers and students. This research is a qualitative study, the research design becomes a reflexive process that operates through each stage of the activity of collecting and analyzing data. Data is collected using literature study techniques and documentation studies, then analyzed by systematic cross-case comparisons from a number of intermediate case studies. From the results of the discussion it can be concluded as follows: 1) STIT Raden Wijaya in the future needs to assess the level of openness and accessibility by developing several forms of index that can be achieved individually or in combination with most of the roadmaps that have been determined. 2) An important part of flexibility for work-based students is the opportunity to negotiate entry and exit points, speed, content, and ratings to suit their work situation which at STIT Raden Wijaya is called educational integration. 3) STIT Raden Wijaya needs to adopt a flexible learning approach to transfer student skills development. This is because 'traditional' learning has proved incapable of developing skills for a diverse student population. 4) describe the skills, knowledge required from academic advisors who work with students through this process. It is a flexible model that can be adapted to the needs, resources and culture of any higher education institution.